2013
DOI: 10.1094/mpmi-04-13-0106-r
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of thetzsGene of NopalineAgrobacterium tumefaciensGV3101 in Plant Regeneration and Genetic Transformation

Abstract: Agrobacterium tumefaciens has been widely used in plant genetic transformation. Hormone-encoding genes residing in the T-DNA region have been removed, resulting in disarmed Agrobacterium strains that are used in various transformation experiments. Nopaline Agrobacterium strains, however, carry another hormone gene, trans-zeatin synthesizing (tzs), that codes for trans-zeatin in the virulence region of the tumor-inducing plasmids. We investigated the activity and function of the tzs gene of a nopaline Agrobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…This is in line with previously published data suggesting that octopine strains lack the tzs gene on their Ti-plasmids, and are thus incapable of secreting high levels of trans -zeatin in culture [30,32]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with previously published data suggesting that octopine strains lack the tzs gene on their Ti-plasmids, and are thus incapable of secreting high levels of trans -zeatin in culture [30,32]. …”
Section: Discussionsupporting
confidence: 92%
“…Cytokinin accumulation in culture was found to be the direct result of the activation of the tzs ( trans-zeatin synthase ) gene [30], an isopentenyl transferase (IPT) gene situated outside of the wild type T-DNA boundaries, in very close proximity to the vir region of the Ti plasmid [30,31]. The tzs gene was not removed during the creation of the disarmed Ti-plasmid pMP90 [17] harbored by GV [32]. The ability of GV cells to stay viable in leaf tissue for more than two weeks after infiltration [9], coupled with our observation that infiltrated tissue developed strong physiological symptoms characteristic of high cytokinin levels (Figure 2H and 2K), suggests that GV is also a constant and significant source of cytokinin in plant tissue in the days following infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic background of the Agrobacterium can influence the T-DNA transfer into plant cellular nuclei, and some Agrobacterium strains are more virulent than others based on the target species 29,30 . In this study, different transformation rates were observed for three avirulent strains.…”
Section: Discussionmentioning
confidence: 99%
“…P CaMV 35S -Osp24 ΔSP was cloned into pGR106 and transformed into A. tumefaciens strain GV3101 90 expressing the BAX and INF1 constructs 91 . For infiltration assays with N. benthamiana leaves, A. tumefaciens cells were resuspended to OD 600 of 0.8 in infiltration solution (10 mM MES, 10 mM MgCl 2 , and 150 μM acetosyringone) 90 .…”
Section: Methodsmentioning
confidence: 99%